Body and testicular traits, libido testing and semen analysis of young males from the Blanco Orejinegro (Bos taurus) herd of University of Antioquia, throughout puberty onset (2001)
ABSTRACT: Fifteen young males (mixed ages) from the BON herd of University of Antioquia were selected and followed weekly from August to December 1998 (Comprising a range from 9,9 to 28,1 months, from 19 time points of data collection) in order to measure and evaluate: 1) Body and Testicular traits (n = 322); 2) Libido testing (LibT, n = 19); 3) Response to rectal palpation of seminal vesicles reflex (SVR, n = 244); and 4) Analysis of semen collected by artificial vagina (n = 42). Data of physical traits were categorized monthly from 10 to 27 months (n = 17 groups); and data of semen were categorized into three groups (16,1 to 21; 21,1 to 24; and 24,1 to 27 months). Simple regression analysis was performed between each trait (dependent variable) and age (independent variable). Multivariate analysis of variance was used to establish differences between groups and monthly reference values for each trait. Physical traits proportionally increased (p<0,01) with age: Body Weight (R2=0,796) and Scrotal Circumference (R2 = 0,672), had the highest correlation coefficients, whereas Body Length (R2 = 0,454), Withers height (R2 = 0,506), Testis Diameter (R2 = 0,415), and Testis Length (R2 = 0,458), had a mild correlation. Higher scores for LibT (more than 5 mating attempts/5 minutes) were always observed. Individual responses to SVR (secretion of pre-seminal fluid, protrusion of penis and complete erection) proportionally increased with age (R2 = 0,539; p<0,01). The youngest age at semen collection was 16,1 months (1,63 x 108 sperm/cc, with >60% gross and individual progressive motility); however, no correlation was found with age, neither for volume (3,6 ml), nor for pH (6,86) or semen concentration. These results suggest the onset of puberty occurs between 13 and 14 months for this BON herd and confirm previous observations on the high libido of BON males. Reference values are reported for both testicular and body traits. Breeding Soundness Examination rather than merely semen concentration must be considered in order to define the onset of puberty in bovine cattle.